Antibacterial evaluation of Styrax pohlii and isolated compounds (Brazilian Journal of Pharmaceutical Sciences, 2013)
The antibacterial activity of the compounds egonol (1) and homoegonol (2), of the crude ethanolic extract of Styrax pohlii (Styracaceae) aerial parts (EE), and of its n-hexane (HF), EtOAc (EF), n-BuOH (BF), and hydromethanolic (HMF) fractions was evaluated against the following microorganisms: Streptococcus pneumoniae (ATCC 6305), S. pyogenes (ATCC 19615), Haemophilus influenzae (ATCC 10211), Pseudomonas aeruginosa (ATCC 27853), and Klebsiella pneumoniae (ATCC 10031). The broth microdilution method was used for determination of the minimum inhibitory concentration (MIC) during preliminary evaluation of antibacterial activity. The EE yielded MIC values of 400 µg/mL for S. pneumoniae and P. aeruginosa and 300 µg/mL for H. influenzae. The HF and EF fractions exhibited enhanced antibacterial activity, with MIC values of 200 µg/mL against S. pneumoniae, but only EF displayed activity against H. influenzae (MIC 200 µg/mL). The best MIC value with compounds 1 and 2 (400 µg/mL) was obtained for (1) against S. pneumoniae and P. aeruginosa. Therefore, 1 exhibited weak antibacterial activity against these standard strains.